1999
DOI: 10.1016/s0006-3495(99)76993-6
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Cushioned Bilayers. II. An Investigation of Interaction Forces and Fusion Using the Surface Forces Apparatus

Abstract: We have created phospholipid bilayers supported on soft polymer "cushions" which act as deformable substrates (see accompanying paper, Wong, J. Y., J. Majewski, M. Seitz, C. K. Park, J. N. Israelachvili, and G. S. Smith. 1999. Biophys. J. 77:1445-1457). In contrast to "solid-supported" membranes, such "soft-supported" membranes can exhibit more natural (higher) fluidity. Our bilayer system was constructed by adsorption of small unilamellar dimyristoylphosphatidylcholine (DMPC) vesicles onto polyethylenimine (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
134
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(140 citation statements)
references
References 50 publications
6
134
0
Order By: Relevance
“…Such a preserved "dynamic behavior" is in good agreement with the recently observed "self-healing" of two polyethylenimine-supported DMPC bilayers after their hemifusion in the surface forces apparatus. 17 In summary, this AFM study provides evidence of tethered lipid bilayer formation by vesicle adsorption onto lipopolymer monolayers. Polymer hydration has been found earlier to be an important factor governing this process.…”
mentioning
confidence: 69%
“…Such a preserved "dynamic behavior" is in good agreement with the recently observed "self-healing" of two polyethylenimine-supported DMPC bilayers after their hemifusion in the surface forces apparatus. 17 In summary, this AFM study provides evidence of tethered lipid bilayer formation by vesicle adsorption onto lipopolymer monolayers. Polymer hydration has been found earlier to be an important factor governing this process.…”
mentioning
confidence: 69%
“…18 This allowed us to study the interaction forces, adhesion, and fusion of lipid bilayers in a more natural state employing the surface forces apparatus (SFA). 19 We found that the presence of the soft polymer cushion significantly alters the interaction between two bilayers, both the long-range force and the fusion pressure, when compared to solid-or rigidly supported systems. Thus, above the main transition temperature of DMPC bilayers (T m ≈ 24 °C), the activation pressure for hemifusion of softly supported bilayers is considerably smaller than for rigidly supported bilayers (i.e., directly supported on mica).…”
Section: Introductionmentioning
confidence: 82%
“…Below T m (in the gel state), very high pressures were needed for hemifusion and the healing process became very slow. 19 In our earlier work, we focused on the effects of the polymer layer on the short-range interaction potential, but we also measured a long-range repulsive force that could not be explained by a purely electrostatic interaction. Furthermore, in structural investigations of our PEI-supported membrane system by neutron reflectivity, we were able to show a significant swelling of the polyelectrolyte cushion separating the lipid membrane from the substrate (quartz).…”
Section: Introductionmentioning
confidence: 99%
“…This happens when their surfaces are dehydrated beyond a critical point, tipping the energetic balance in favor of radically curved nonbilayer structures (such as inverted hexagonal phases, rhombohedral phases) 71, 72. An analogous abrupt transition is also observed when two bilayers are directly pressured together in the surfaces forces apparatus 73. Following on this pioneering work, detailed measurements suggest that the transition pressure is in the range of 200–500 atm (one atm is the typical pressure of the atmosphere at sea level) for lipid compositions bracketing the inner leaflets of the SV and PM (see Appendix 1 for details) 48, 49.…”
Section: Quantitative Considerationsmentioning
confidence: 99%